INVESTASI SEBAGAI DETERMINAN PRODUK DOMESTIK REGIONAL BRUTO DI INDONESIA: TINJAUAN LITERATUR ATAS BUKTI EMPIRIS DAN ARAH PENELITIAN MENDATANG - Erna; Athaillah Adwitiya; Fajriyatul Abadiyah (Adpertens: Jurnal Ekonomi dan Manajemen, 2026)
Regional economic growth in Indonesia is measured by the Regional Gross Domestic Product (RGDP), with investment being one of the most frequently associated factors. However, the findings of various previous studies have not always been consistent, so the relationship between investment and RGDP requires further examination. This study aims to summarize, compare, and analyze investment-RDP relationship patterns in Indonesia based on existing research. The method used is a literature review employing a descriptive-comparative qualitative approach. Data sources were drawn from Sinta-accredited national scientific journals and relevant peer-reviewed articles, identified through Google Scholar, Garuda, and the Sinta journal portal. The findings indicate that investment generally has a positive impact on GRDP across various regions in Indonesia; however, the magnitude of this contribution is heavily determined by a region’s capacity to absorb and optimize incoming capital. Human resource quality, labor market conditions, and local government governance capacity have been shown to moderate investment effectiveness on GRDP growth. The disparity in investment distribution between Java and non-Java regions reflects structural disparities in inter-regional capacity. This study confirms that investment effectiveness is not determined solely by the investment magnitude, but rather by the quality of the supporting ecosystem in which it is carried out.